Nevropsihološka diagnostika sposobnosti prepoznavanja in celostnega združevanja informacij - možnosti za ocenjevanje, trening in kognitivno nevrorehabilitacijo - Starovasnik, Barbara (Rehabilitacija (Ljubljana), 2012)
Agnosias develop when the meaning is striped from a percept, and there are problems associated with the cortical processing of stimuli which are not related to or can be explained by deficits in the sensory organ. Traditionally, a distinction between apperceptive and associative forms of agnosia has been made, and due to some modality specifics several types of agnosia have been identified (visual, auditory, tactile). Anosognosia refers to patients suffering from various neurological impairments who deny or lack awareness of their deficits, although these deficits may have serious consequences in their everyday life, rehabilitation process and/or their recovery from initial disease. We are still not aware of any controlled study of therapy for anosognosia in cases of, for example, hemiplegia. Rather, patients should be examined to determine the extent and the nature of their complete syndrome of impaired awareness individually or as group therapy settings. Neuropsychological assessment has two fundamental goals. First, the possibility that recognition disturbance exists because of some other co-existing impairment, which should be ruled out with standardized neuropsychological testing instruments. Second, the scope and nature of the patient's recognition disturbance should also be assessed and determined. Key symptoms, characteristic neuroradiological findings, and a general neuropsychological approach based on cognitive neuropsychological models of object recognition is an important differential and diagnostic tool. Although significant progress has recently been made, much remains to be learned and explored about these complex disorders.
Keywords: Agnosia; agnozija; anosognosia; anozognozija; Diagnosis, Differential; diferencialna diagnostika; neuropsychological rehabilitation; nevropsihološka rehabilitacija